Działalność archeologiczna Towarzystwa Naukowego w Toruniu w Borach Tucholskich do 1914 - Grabarczyk, Tadeusz (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
In the first years following its foundation in 1875, the Toruń Scientific Society was archaeologically very active within the Tuchola Forests. In this early period, particularly great services were rendered by Godfryd Ossowski who in 1876-1878 examined a number of cemeteries. Later, this activity was reduced though in the early 20th century a priest, Kazimierz Chmielecki, still showed certain interest in these problems. After World War I the Society virtually ceased to take interest in archaeology.